Digital and Interpersonal Skills in Higher Education: A Qualitative Analysis of International Teaching Practices - Ouariach, Fatima Zahra; Ouariach, Soufiane (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
This study explores the integration of digital and interpersonal skills in higher education through a qualitative analysis of international teaching practices. Based on interviews with five professors from various academic institutions around the world, the findings reveal major challenges, such as unequal access to technology, resistance to pedagogical change and the erosion of interpersonal skills due to excessive use of digital communication. Educators recommend mixed strategies such as project-based learning, gamification, mentoring and interactive tools to develop these two skills in parallel. The study concludes that these skills are not only complementary, but also essential to student adaptability and success in hybrid learning and professional environments, prompting universities to adopt integrated pedagogical approaches and strengthen faculty development.